Speech Recognition for the Sterile Interaction with Information Systems in the Surgical Area - Schrüfer Katrin V.; Noortwijck Pascal; Junger Denise; Burgert Oliver (Current Directions in Biomedical Engineering)
This paper describes how automatic speech recognition (ASR) can be used to explore electronic patient records (EPR) in a sterile environment. As an information display, we used a system that was developed for the presentation of patient data and for supporting surgical hand disinfection. The speech recognition was performed using the Mozilla Web Speech API. A room microphone, a Jabra Box, and a directional microphone, a RØDE NT-USB Mini, were tested at various positions. Interactions with the EPR are triggered with a list of commands. The interaction was working as indented and test persons reported the system as intuitive.